South Africa's emerging black middle class: A harbinger of political change? - Robert Mattes (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
South Africa has seen a significant increase in the size of the black middle class in the post-apartheid period, but the attitudinal consequences of indicators of the middle class, as of 2011, are inconsistent and modest in size. While members of the middle class are no more likely to hold democratic values than other black South Africans, they are more likely to want government to secure higher order, rather than basic, survival needs. They are less likely to identify with the governing African National Congress, turn out to vote, or voice their concerns by contacting officials or joining collective action. At the same time, intra-racial differences between middle class black respondents, on one hand, and middle class white, coloured and Indian respondents, on the other, are still substantial.
Keywords: 330; South Africa; middle class; attitudes; survey; research; democracy